Magical tales myth, legend and enchantment in children's books - Larrington, Carolyne; Purkiss, Diane 1961- (Bodleian Library, University of Oxford, 2013)
A faun carrying an umbrella; a hobbit who lives in a hole; a mysterious name, Lyra; an ill-treated schoolboy with a scar and a secret. Children's fantasy books often begin with resonant images. However, they also begin in an author's reading practices. How do children's authors incorporate myths and legends into their work? And how do myths and legends change as a result? In this illustrated collection of essays a team of academic experts trace the magical tales from Norse myth, Arthurian legend and medieval literature which have inspired the finest writers for children, including C.S. Lewis, J.R.R. Tolkien and Alan Garner. Drawing on collections of manuscripts and rare books in the Bodleian Library, additional chapters put the spotlight on spell books, grimoires and books that do magic, as well as exploring stunning examples of pop-up books, harlequinades and concertina panoramas from the Opie Collection of Children's Literature. Other writers under discussion include children's authors of the Victorian era, such as George MacDonald, Rudyard Kipling and E. Nesbit, and twentieth-century writers Susan Cooper, Diana Wynne Jones and Philip Pullman.Through wide-ranging analysis these essays show how literature and tales from the Middle Ages and earlier still have been reinterpreted for each generation and continue to have a profound impact on writers of fantasy books for children today.